The Mental Health of the Migrant Patient: Between Medicalisation and the Expression of Social Suffering - Bova, Roberta (Italian Sociological Review, 2022)
This article analyses the Italian social and health services accessed by migrants suffering from mental disorders. The aim of the article is to identify the effective accessibility of care facilities, and the dynamics of discrimination, negotiation, and dialogue that come to life in the interactions between socio-health workers and migrants. The article is based on the fieldwork research I conducted in a province in Northwest Italy between 2019 and 2020, in the network of the mental health services. The research was based on a mixed-method approach, and first analysed the epidemiological data regarding access to mental health services by the migrant population and the prevalent diagnoses. Subsequently, I carried out 22 discursive interviews with various professionals who work in this sector. In the light of the data collected, two main issues emerge: (a) the negotiation carried out by professionals between the social pressures for a return to a form of repressive psychiatry and the cultural expression of social needs stated by immigrant patients, and (b) the problematisation of the distinction between social suffering and mental disorder. Both issues refer to the process of medicalisation of mental health. The paper discusses the phenomena mentioned above through the analysis of the empirical material collected, and in relation to the scientific literature on the subject.